APPLICATION OF IMMUNOSTIMULANTS TO ADDRESS THE ACUTE RESPIRATORY INFECTIONS AMONG CHILDREN. FOREIGN EXPERIENCE - EVIDENCE BASED MEDICINE VIEWPOINT - A.S. Kolbin; A.V. Kharchev (Union of pediatricians of Russia, 2007)
Acute respiratory infections are one of the main reasons for the morbidity among children. In this respect, one of the urgent trends in the modern medicine is believed to be prophylaxis of these diseases, including immunostimulant aided prevention. However, use of the medications from this group is highly debatable. Like wise many doctors skeptically view their use. The objective of the conducted research was to analyze the international clinical research with immunostimulants among children from the evidentbased medicine viewpoint. As a result of the electronic research, the authors have found out 122,189 links, 88 of which were identified as clinical research. As a consequence, the analysis incorporated 34 research works, comprising 3,727 children and 1 meta analysis. Due to the high prevalence of the methodic drawbacks during the clinical research, the efficiency calculation was conducted only on the basis of the data on the bacterial immuno stimulants. The work showed that they would decrease the general number of the respiratory infections by 1,7 (95% confidence interval of 1,54-1,86). The frequency of the unwanted effects was pretty low and no different from placebo groups. The authors believe that it is necessary to conduct Russian randomized placebo controlled multi centered clinical research among children to finally clarify the efficiency and safety of immuno stimulants for the prevention of the respiratory infections.Key words: immunostimulants, аcute respiratory tract infections, children.